Diagnostico técnico económico del cultivo de tomate riñón (Solanum lycopersicum) bajo condiciones de invernadero y a campo abierto en el Cantón Bolívar, Provincia del Carchi - Escobar Manrique, Jose Félix (2018)
ABSTRAC While in the country, agriculture is a cornerstone in thedevelopment of the economy, there is hardly any innovation, farmers have received little or no training, their own technology has not been developed in the field. Farmers' incomes depend exclusively on the sale of their products to a highly volatile market in prices. The present work makes an analysis of the costs production, in order to analyze the production in the open field or greenhouse, to provide a tool that allows to have the record of the investment made. An analysis of the costs of production of one hectare of tomato kidney (Solanum lycopersicum) in the Bolívar canton of the province of Carchi, for crops in the open field and under greenhouse, presents the structure of costs production, with details on the number of irrigation carried out, the cultural work made, the amounts of fertilizers and agrochemicals applied, supplies, equipment, tools, etc. that have been used in the mentioned production systems. The diagnosis of the costs production for the two systems is obtained, noting that a large initial investment is necessary for greenhouse cultivation, with the advantage that climatic conditions can be controlled and thus intensify production, thus recovering the initial investment in a short time, depending on the costs of sale. This work is a tool for planning and decision making, so that the producer or investor can decide on the choice of the productive system, and can obtain a profitability of their product; improving the quality of life.